Correlation of the Second Derivative of Digital Pulse Wave (DPW) with Central Obesity in Women - Husain A. Al-Byatee, Amal Y. M. Al-Yasiri, Bassam T. Al-Gailani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity, as measured by body mass index (BMI) or measures of central obesity, including waist-to-hip ratio (WHR) and waist circumference, is related to higher total and cardiovascular mortality. Four systolic waves (a, b, c, and d) and one diastolic wave (e) make up the second derivative of the digital pulse wave (SDPTG), which is obtained by two mathematical differentiation of the original PTG. Objective: To find out whether the (SDDPW) is correlated with central obesity in women. Methods: 55 healthy female subjects with Body Mass Index (31.5±7.3) were included in the current study. A fingertip pulse wave transducer was used to record digital pulse waves. For automatic detection and measurement of A, B, C, D, and E waves and amplitude of the second derivative digital pulse wave, Lab Chart Pro version 7.2 was used. Height and weight were measured. Waist and hip circumference were measured. Brachial systolic and diastolic blood pressures (SBP & DBP) were measured. Results: The results showed that B/A ratio is positively and significantly affected by central obesity in terms of waist circumference (r = 0.3, P<0.037), and waist/height ratio (r = 0.31, P<0.031). Conclusion: B/A ratio is positively and significantly affected by central obesity.